Towards an adaptive QoS-driven monitoring of cloud SaaS. (1st January 2014) - Serhani, Mohamed Adel; Atif, Yacine; Benharref, Abdelghani
The abundance of services offered by cloud providers raises the need for Quality of Service (QoS) monitoring to enforce Service Level Agreements (SLAs). In this paper, we propose a cloud-monitoring scheme, which offers flexible and dynamically reconfigurable QoS monitoring services to adapt to various cloud based service characteristics. We propose to grant cloud service consumers the option to decide whether to switch to another service provider, if the current provider frequently violates the corresponding SLA contract. For cloud service providers, the monitoring scheme provides dashboard-like indicators to continuously manage the performance of their SaaS platform and visualise the monitoring data. Our experimental evaluation involves a real cloud platform to illustrate the capability of our monitoring scheme in detecting and reporting violations of SLAs for both single and composite SaaS services. A particular emphasis on visualisation options is highlighted when revealing and reconfiguring monitoring data in a user-friendly display.